1998
DOI: 10.1038/eye.1998.99
|View full text |Cite
|
Sign up to set email alerts
|

Dark adaptation in early primary biliary cirrhosis

Abstract: Patients with early PBC have modestly impaired dark adaptation, despite standard vitamin A supplementation, although these changes may not have a significant effect on visual function. Vitamin A supplementation should be recommended for older patients with jaundice, but its effect should be carefully monitored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…However, it is difficult to compare the final light threshold of any group of this study with absolute figures of other dark adaptation study results with any degree of validity and sense. The problem arises from the fact that investigators used various techniques and methods (Goldman-weekers, Friedmann visual field analyzer, pupillary threshold method, etc) to assess scoropic vision pattern (Hussaini et al, 1998;Herlong et al, 1981;Congdon et al, 2000). Methods vary in defining dark adaptation, their calibration and spectral composition, initial dark adaptation level, age, sex grouping etc.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is difficult to compare the final light threshold of any group of this study with absolute figures of other dark adaptation study results with any degree of validity and sense. The problem arises from the fact that investigators used various techniques and methods (Goldman-weekers, Friedmann visual field analyzer, pupillary threshold method, etc) to assess scoropic vision pattern (Hussaini et al, 1998;Herlong et al, 1981;Congdon et al, 2000). Methods vary in defining dark adaptation, their calibration and spectral composition, initial dark adaptation level, age, sex grouping etc.…”
Section: Discussionmentioning
confidence: 99%
“…8 Subjects were excluded from the study if they had choroidal neovascularization, geographic atrophy, OCT, or FAF signs of atrophy or nascent GA, 9 and any other ocular disease that could compromise visual function, including glaucoma, significant cataracts ( ‡2 score on the Age-Related Eye Disease Study [AREDS] cataract grading system 10 ), diabetic retinopathy, amblyopia, history of previous eye surgery, and medications known to affect retinal function, such as hydroxychloroquine. In addition, subjects with medical conditions that could affect dark adaptation (such as liver disease 11 and renal disease 12 ) also were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Underperception of night blindness has been reported by others in ALD,13 PBC14 24 and also in malnutrition. Our study confirmed underperception of impairment of DA which is a risk to patient safety.…”
Section: Discussionmentioning
confidence: 71%